Students Perception on the Vocabulary Translation in Learning English at the Second Grade of SMKN 4 Payakumbuh - Amalia Ulfa; Arifmiboy; Reflinda; Veni Roza (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2022)
The research was due to several problems found in the field: the students less vocabulary in English. It was indicated when I tried asked some students to translate about some vocabulary, some of students knew the the meaning of those vocabulary but much of the students did not knew what the meaning is. The research is aimed to find out students perception on vocabulary translation in Learning English at the second grade students of SMKN 4 Payakumbuh.The research used descriptive quantitative research by using questionnaire as an instrument. The result of the research: first students perception on word to word method with 26,7% in rating quality is almost of half with the mean of the respondent’s answer moderate option. Second, students perception on free translation method with 30,2% in rating quality is almost of half with the mean of the respondent’s answer moderate option. students perception on teacher’s facial expression with 36,4% in rating quality of good. Third, students perception on literal translation method with 25,02% in rating quality is fraction with the mean of the respondent’s answer is hard option. It can be concluded that almost of half students have moderate opinion about all indicator of translate method on vocabulary translation in Learning English at the seventh grade students of SMKN 4 Payakumbuh in Academic Year 2020/2021.